Fa’āliyyah Barnāmaj Nafsī Lita’zīz al-Murūnah al-Fīsiyūlūjiyyah lada al-Nisā’ al-Mu’annifāt: فعالية برنامج نفسي لتعزيز المرونة الفسيولوجية لدى النساء المعنفات - Mousa, Shireen Safar; Omar, Jehan Hussein (Study Program of Arabic Language Teaching, 2025)
This research aimed to measure the effectiveness of a psychological program in enhancing physiological resilience represented by cortisol and C-reactive protein (CRP) levels among Syrian refugee abused women in Domiz camp in Duhok governorate. The researchers used a quasi-experimental design with a single group and pre-post measurements. The research sample consisted of (20) Syrian refugee abused women selected purposively. A psychological program consisting of (16) sessions distributed over seven weeks was applied, and cortisol and CRP levels in blood were measured before and after the program implementation. Results showed a statistically significant decrease in cortisol levels from (436.30) to (289.30) with a calculated t-value of (4.01), while no significant changes were observed in CRP levels. The researchers recommend implementing similar psychological programs with longer application periods to enhance the effect on inflammatory indicators.